2015
DOI: 10.1371/journal.pone.0142125
|View full text |Cite
|
Sign up to set email alerts
|

Unreliable Tracking Ability of the Third-Generation FloTrac/Vigileo™ System for Changes in Stroke Volume after Fluid Administration in Patients with High Systemic Vascular Resistance during Laparoscopic Surgery

Abstract: BackgroundThe FloTrac/Vigileo™ system does not thoroughly reflect variable arterial tones, due to a lack of external calibration. The ability of this system to measure stroke volume and track its changes after fluid administration has not been fully evaluated in patients with the high systemic vascular resistance that can develop during laparoscopic surgery.MethodsIn 42 patients undergoing laparoscopic prostatectomy, the stroke volume derived by the third-generation FloTrac/Vigileo™ system (SV-Vigileo), the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Chin et al compared the SV derived by a radial artery uncalibrated pulse-contour method (the third generation FloTrac/Vigileo system, Edwards Lifesciences, Irvine, California, USA) with the SV derived by TEE Doppler in patients undergoing laparoscopic prostatectomy. [30] The percentage errors of the absolute values was 53.8%, with a concordance rate of 69.2% (four-quadrant plot), and the mean angular bias 20.6 degrees with radial limits of agreement of ±51.5 degrees in the polar plot. They concluded that the third-generation FloTrac/Vigileo system was not reliable in measuring SV or in tracking changes in the SV after fluid administration in the high systemic vascular resistance state.…”
Section: Discussionmentioning
confidence: 98%
“…Chin et al compared the SV derived by a radial artery uncalibrated pulse-contour method (the third generation FloTrac/Vigileo system, Edwards Lifesciences, Irvine, California, USA) with the SV derived by TEE Doppler in patients undergoing laparoscopic prostatectomy. [30] The percentage errors of the absolute values was 53.8%, with a concordance rate of 69.2% (four-quadrant plot), and the mean angular bias 20.6 degrees with radial limits of agreement of ±51.5 degrees in the polar plot. They concluded that the third-generation FloTrac/Vigileo system was not reliable in measuring SV or in tracking changes in the SV after fluid administration in the high systemic vascular resistance state.…”
Section: Discussionmentioning
confidence: 98%
“…Dynamic monitoring indices guide fluid replacement [ 5 ] but are not very reliable in the context of minimally invasive surgery. [ 6 7 ] This obligates a fluid management based upon haemodynamic profile, urine output and metabolic parameters such as lactate, which is an early indicator of tissue hypoperfusion. [ 8 ] The restrictive versus liberal fluid therapy in major abdominal surgery (RELIEF) trial [ 9 ] while comparing a restrictive versus liberal fluid administration strategy has shown increased risk of renal failure, renal replacement therapy and surgical site infection in the restrictive group.…”
Section: Discussionmentioning
confidence: 99%
“…The pulse contour systems (LiDCO and Vigileo) that were utilized for both studies have shown difficulty in tracking changes in CI. [181920] We used the latest software version for the FloTrac system, which has shown improved accuracy in measuring CI in patients with varying systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%